The Role Of Pathomorphology In Early Detection Of Gynecological Cancers: Challenges And Advances (Open Herald: Periodical of Methodical Research, 2025)
The early detection of gynecological cancers remains a critical challenge in improving patient outcomes. Pathomorphology, the study of tissue changes at the microscopic level, plays a pivotal role in identifying precancerous lesions and early-stage malignancies in gynecological tissues. This article explores the contributions of pathomorphology in the early diagnosis of gynecological cancers, focusing on its role in the histopathological examination of cervical, ovarian, and endometrial cancers. It discusses the challenges faced, such as the difficulty in distinguishing benign from malignant lesions, and highlights recent advances in diagnostic techniques, including immunohistochemistry, molecular pathology, and the integration of artificial intelligence in diagnostic workflows. The article concludes by emphasizing the potential of pathomorphology in developing personalized treatment plans and its importance in enhancing the overall prognosis for gynecological cancer patients.